Blood-flow restricted exercise following ankle fractures — A feasibility study. Issue 6 (August 2022) - Larsen, Peter; Platzer, Oscar Just; Lollesgaard, Lærke; Pedersen, Samuel Krogh; Nielsen, Peter Kruse; Rathleff, Michael S.; Bandholm, Thomas; Jensen, Stefan Teglhus; Elsoe, Rasmus
Highlights: Early use of BFRE in patients with unilateral ankle fractures seems feasible. Results indicate very high degree of patient acceptance of pain and discomfort. BFRE training may represent the potential to facilitate a rapid rehabilitation following an ankle fracture. Abstract: Background: The objective was to investigate the feasibility of blood flow restricted exercise (BFRE) as a rehabilitation modality in patients with a unilateral ankle fracture. Methods: Feasibility study with a prospective cohort design. Inclusion criteria were above 18 years of age and unilateral ankle fractures. Exclusion criteria: history of cardiac or embolic diseases, cancer, diabetes, hypertension and family history of cardio or vascular diseases. The predefined feasibility outcome was based on three criteria regarding patients experience with participating in the BFRE protocol and the absence of any serious adverse events. Results: Eight patients were included. Median age was 33 years (range: 23−60). All eight patients reported maximum satisfaction on the two questions regarding patient's perception of the overall experience with BFRE training and the feasibility to introduce BFRE as an intervention. Conclusion: Early use of BFRE in patients with unilateral ankle fractures seems feasible in patients without comorbidity.